The Influence of Using Gist Strategy Towards Students’ Reading Comprehension at The Eighth Grade Junior High School - Pradana, Satria Adi; Khasanah, Aniswatun (English Education: Jurnal Tadris Bahasa Inggris, 2022)
Online  learning chosen to be applied in almost all of schools in Indonesia, but now in condition many school in Indonesia has applied offline learning, this also applied to SMPN 2 Way Jepara East Lampung. GIST strategy to discover important information and idea in a text, and they could schematize descriptive texts in their own language to make them easier to understand. The aims this study was to determine students reading comprehension. This research was conducted with a quantitative method. This subject of this study were 63 students were sampled from 2 courses, VIII1 and VIII 2. The data was collected by using a multiple choice test as an instrument using pre-test and post-test. The independent t-test result was 0.020 with a significance of 0.05, according to the data analysis. The score of t-observed was higher than t-crucial (0.05) in the analysis, so H0 was rejected. It means that the GIST strategy has an influence on students' reading comprehension, especially in descriptive text. So, on there is an influence of employing the GIST strategy on students’ reading comprehension of descriptive text.